A Rare Case of Limb Body Wall Complex Associated with Environmental Mercury Exposure and Maternal Herpes Infection - I Gde Hary Eka Adnyana; Dwi Andhika Panjarwanto; Prima Aulia Achsan; Agus Rusdhy Hariawan Hamid; Ario Danianto (Green Publisher Indonesia, 2026)
Limb body wall complex (LBWC) is a rare and fatal congenital anomaly involving severe defects of the body wall, spine, limbs, and umbilical cord. This study aims to report a rare case of LBWC associated with environmental mercury exposure and maternal herpes infection, to review the literature on LBWC pathogenesis and risk factors, and to generate hypotheses for future etiological research. Early prenatal diagnosis is crucial; however, cases may be detected late in settings with limited antenatal care. We report a 37-year-old multiparous woman in whom LBWC was diagnosed by ultrasonography at 24–25 weeks' gestation. Imaging revealed a large abdominal wall defect with exposed intestinal loops, spinal deformity, limb dysplasia, and a short umbilical cord — findings that were confirmed postnatally. Maternal assessment identified active HSV-1/2 infection and residence near gold-mining activities, suggesting possible environmental mercury exposure. LBWC remains a devastating and fatal congenital condition. This case emphasizes the critical role of early antenatal screening and highlights the need for further research exploring possible associations between LBWC, maternal infections, and environmental exposures, particularly mercury exposure in gold-mining areas.